IOP lowering effects of ocimum basilicum seed extract in two rabbit models of ocular hypertension / Renu Agarwal … [et al.] - Agarwal, Renu; Gupta, SK; Srivastava, Sushma; Saxena, Rohit (Universiti Teknologi MARA Cawangan Selangor, 2019)
Ocimum basilicum (OB), a herb known for its antihypertensive, anticholinesterase and antioxidant properties was investigated for possible intraocular pressure (IOP) lowering effects in rabbits with ocular hypertension (OHT). Methods: The IOP lowering effect of a single drop of OB extract (OBE) was evaluated in oculonormotensive rabbits using three concentrations (0.25, 0.5 and 1% w/v). The concentration showing maximum IOP reduction was further evaluated in rabbits with water-loading and steroidinduced OHT. Results: IOP lowering effect of OBE 0.5% in oculonormotensive rabbit eyes was significantly greater compared to OBE 0.25% (p0.05) to OBE 1%. Therefore, 0.5% concentration was selected for further evaluation. Pretreatment with OBE (0.5%) caused significantly lower increase in IOP after water loading amounting to 23.39% above baseline as compared to 54.00% in control eye, 15 minutes post water loading. At 60 minutes, post water loading, mean IOP rise was 95.12% and 63.58% in control and test eyes, respectively. Significant difference between the mean IOP of two eyes persisted during the 2nd hr. In rabbits with steroid induced OHT, OBE 0.5% produced a mean IOP reduction of 24.73% at the end of first hr and the mean peak IOP reduction of 31.63% was observed at the end of 2 hr. A significant difference between the IOP of test and control eyes persisted from 1 to 6 hr. Conclusions: Ocimum basilicum seed extract showed significant IOP lowering effect in rabbits with water loading and steroid induced OHT, however, its utility as an effective antiglaucoma medication needs further investigations.